Strategic Planning And Recruitment Of Islamic Education Personnel At Madrasah Ibtidaiyah Ta’allumussibyan - Dennis Haruna; Zulfani Sesmiarni (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to analyze human resource planning and recruitment at Madrasah Ibtidaiyah (MI) Ta'allumussibyan in the context of Islamic education. Professional and spiritually integrated human resources are key to the success of Islamic educational institutions. Using a quantitative descriptive approach, data was collected from 13 teachers using a questionnaire consisting of 30 statements related to two main sub-variables: HR planning and recruitment. The results of the analysis show that the HR planning aspect received an average score of 4.29, while recruitment received a higher score of 4.53. This reflects that MI Ta'allumussibyan has implemented a fairly effective HR management system that is in line with Islamic values. The findings indicate that planning has been aligned with the madrasah's vision and mission and the actual needs of educators, although formal documentation and long-term planning still need to be improved. On the other hand, the recruitment process shows high professionalism, with assessments of the ability to read the Qur'an, understanding of Islamic values, and the involvement of religious leaders in the selection process. However, there are still weaknesses in the transparency of the selection assessment system and the potential for nepotism. This study recommends improvements in policy documentation and broader stakeholder involvement in the planning and recruitment processes. By strengthening data-driven strategies and spiritual values, the madrasah can enhance the quality of Islamic education sustainably. The findings of this study are also relevant as a reference for other madrasahs with similar characteristics.